Targeted Alpha Therapy: Progress in Radionuclide Production, Radiochemistry and Applications - Bryce J. B. Nelson (Pharmaceutics, 2021)
This review outlines the accomplishments and potential developments of targeted alpha (α) particle therapy (TAT). It discusses the therapeutic advantages of the short and highly ionizing path of α-particle emissions; the ability of TAT to complement and provide superior efficacy over existing forms of radiotherapy; the physical decay properties and radiochemistry of common α-emitters, including 225Ac, 213Bi, 224Ra, 212Pb, 227Th, 223Ra, 211At, and 149Tb; the production techniques and proper handling of α-emitters in a radiopharmacy; recent preclinical developments; ongoing and completed clinical trials; and an outlook on the future of TAT.